IMPLEMENTASI KOTA RAMAH ANAK (STUDI KEBIJAKAN KARTU IDENTITAS ANAK BERBASIS KLAMPID KOTA SURABAYA) - Khofifah Agustina Hardiyanti; Singgih Manggalou (Jurnal AKTUAL, 2022)
The Child Identity Card (KIA) policy is a policy breakthrough as outlined in the Ministry of Home Affairs Regulation (Kemendagri) No. 2 of 2016 concerning Child Identity Cards (KIA). MCH includes the protection and implementation of children's constitutional rights as a sign for the unmarried population under the age of 17 years. For this reason, researchers conducted research at the Surabaya City Population and Civil Registration Service or Dispendukcapil Surabaya which is responsible and authorized to provide services in the field of population administration. Disdukcapil Surabaya also implements a Child Identity Card (KIA) policy. The Child Identity Card program has been implemented in the city of Surabaya since mid-2019. By the end of 2021, 370,833 children have had KIA in the city of Surabaya, while 404,856 children have not had KIA. The implementation of the Child Identity Card Policy in the City of Surabaya is considered effective and will later innovate. This study aims to determine how the implementation of child-friendly cities (Study of Child Identity Card Policy Based on Klampid Surabaya City). This research uses descriptive research with a qualitative approach. Data collection techniques used to draw conclusions are interviews.